Marijuana on main street: What if? - Liana Jacobi; Sovinsky Michelle (University of Zurich, Department of Economics, 2012)
Illicit drug use is prevalent around the world. While the nature of the market makes it difficult to determine the total sales worldwide with certainty, estimates suggest sales are around 150 billion dollar a year in the United States alone. Among illicit drugs marijuana is the most commonly used, where the US government spends upwards of 7.7 billion per year in enforcement of the laws for marijuana sales (Miron, 2005). For the past 30 years there has been a debate regarding whether marijuana should be legalized. There are two important avenues through which legalization could impact use: legalization would make marijuana easier to get, and it would remove the stigma (and cost) associated with illegal behavior. Studies to date have not disentangled the impact of limited accessibility from consumption decisions based solely on preferences. However, this distinction is particularly important in the market for cannabis as legalizing the drug would impact accessibility. Hence, if most individuals do not use because they don't know where to buy it, but would otherwise use, we would see a large increase in consumption ceteris paribus, which would be important to consider for policy. On the other hand, if accessibility plays little role in consumption decisions, then making drugs more readily available would impact the supply more. In order to access the impact of legalization on use, it is necessary to explicitly consider the role played by accessibility in use, the impact of illegal actions in utility, as well as the impact on the supply side. In this paper, we develop and estimate a model of buyer behavior that explicitly considers the impact of illegal behavior on utility as well as the impact of limited accessibility (either knowing where to buy or being offered) an illicit drug on using the drug. We use the demand side estimates to conduct counterfactuals on how use would change under a policy of legalization. We conduct counterfactuals under different assumptions regarding how legalization would impact the supply as well as various tax policies on the price of cannabis.
Keywords: 330; Cannabis; Nachfrage; Legalisierung; Drogenkonsum; Konsumentenverhalten; Welt